Systematic study of the parabola with the contribution of GeoGebra software as a teaching proposal - de Sousa, Renata Teófilo; Vieira Alves, Francisco Régis; Souza, Maria José Araújo (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
This work aims to present different demonstrations of the parabola, as well as possibilities of its geometric construction, using geometric design techniques and the GeoGebra dynamic geometry software. The methodology of this work is a basic theoretical research, exploratory type, in which we seek to bring a view about the parabola focused on improving its teaching as mathematical knowledge with the contribution of GeoGebra software. As a result, we bring a set of five constructions made in GeoGebra and available for use, which can be used as a methodological resource by the teacher to work in the classroom. As this work is part of an ongoing master's research, as future perspectives, we aim to develop these constructions in the classroom and collect empirical data for further analysis and discussion.